Experimental and modeling study of foam coarsening kinetics in porous media - Yu, Wei; Zhou, Xianmin (Frontiers in Energy Research, 2022)
The geometric confinement significantly affects the foam coarsening dynamics in porous media. We present the experimental and modeling studies of coarsening-induced foam structural evolution in a porous microfluidic chip. The findings are expected to shed light on the prediction of the foam structure in many applications, such as foam-assisted enhanced oil recovery process and CO2 geological sequestration. It is shown that, in porous media, small bubbles are constantly consumed by large bubbles due to inter-bubble gas diffusion until most bubbles grow to the pore or throat size. The coarsening of edge bubbles (bubbles contacting the boundary) dominates the foam coarsening process, showing a linear increase in the average area of edge bubbles with time in a steady-state growth state. A mass transfer model is proposed to fit the foam coarsening rate of edge bubbles, including critical parameters such as liquid film permeability, gas-liquid interfacial tension, the molar volume of the dispersed phase, and the polydispersity of bubble size distribution. We emphasize that, under the same experimental conditions, foams with a broader size distribution can exhibit a faster coarsening rate due to higher capillary pressure differences among the bubbles as the mass transfer driving force.